The Making of Geometry. (2015) - Bertol, Daniela
Abstract: Geometry has been a source of inspiration in the design of the manmade world for millennia; it also provides representational means enabling development of a concept into a built object. In the past three decades computing methodologies have provided the designer with unprecedented tools to explore highly complex forms, create digital models and fabricate them. This paper describes a computational methodology for the transition of forms from abstract geometric configurations to physical objects: a parametric design process assists from the initial ideation to the final prototyping with 3D printing technologies. The five regular polyhedra are used as a case study; this paper explores how parametric based procedures develop these geometric shapes into digital models of structures to be fabricated in different sizes and materials.